Convergent microevolution of Cryptococcus neoformans hypervirulence in the laboratory and the clinic. Issue 1 (December 2017) - Arras, Samantha; Ormerod, Kate; Erpf, Paige; Espinosa, Monica; Carpenter, Alex; Blundell, Ross; Stowasser, Samantha; Schulz, Benjamin; Tanurdzic, Milos; Fraser, James
Abstract Reference strains are a key component of laboratory research, providing a common background allowing for comparisons across a community of researchers. However, laboratory passage of these strains has been shown to lead to reduced fitness and the attenuation of virulence in some species. In this study we show the opposite in the fungal pathogenCryptococcus neoformans, with analysis of a collection of type strain H99 subcultures revealing that the most commonly used laboratory subcultures belong to a mutant lineage of the type strain that is hypervirulent. The pleiotropic mutant phenotypes in this H99L (for "Laboratory") lineage are the result of a deletion in the gene encoding the SAGA Associated Factor Sgf29, a mutation that is also present in the widely-used H99L-derived KN99a /α congenic pair. At a molecular level, loss of this gene results in a reduction in histone H3K9 acetylation. Remarkably, analysis of clinical isolates identified loss of functionSGF29 mutations inC. neoformans strains infecting two of fourteen patients, demonstrating not only the first example of hypervirulence in clinicalC. neoformans samples, but also parallels betweenin vitro andin vivo microevolution for hypervirulence in this important pathogen.